-(x+4)=7

Simple and best practice solution for -(x+4)=7 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -(x+4)=7 equation:


Simplifying
-1(x + 4) = 7

Reorder the terms:
-1(4 + x) = 7
(4 * -1 + x * -1) = 7
(-4 + -1x) = 7

Solving
-4 + -1x = 7

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '4' to each side of the equation.
-4 + 4 + -1x = 7 + 4

Combine like terms: -4 + 4 = 0
0 + -1x = 7 + 4
-1x = 7 + 4

Combine like terms: 7 + 4 = 11
-1x = 11

Divide each side by '-1'.
x = -11

Simplifying
x = -11

See similar equations:

| 7/20 | | 5a+2b-4=0 | | 40-2x=5-9x | | 9(x+5)+7(x+5)=7x-7 | | a+1=a-5*3 | | 6x+18-5x=-8-12 | | a-2b-4=0 | | (4/x)=8 | | 2y^2-6y+9=25 | | 3x+59=8x+9 | | 7x+5=201 | | 15r-6+10-3r=40 | | a-5*3=a+1 | | 4x+9=2x-35 | | (-3+7i)(1-2i)=0 | | 2y^2-6y-16=0 | | 4x=2(6x+4) | | 5x-15/3=-20 | | 3x-1=10x-65 | | 4(x-15)=500 | | 8t+8=3(2t+5) | | 4x=12-(-12) | | -2x+y+6=0 | | 6.14x+36.84=73.68 | | 3x-14=3x+4 | | -x-1/5=6 | | 4+78x=39x+10 | | 16/-7=20/x | | a-5=3*a-5+1 | | X/-3-5=-9 | | -5(x+2)-17=11+7 | | 11x+4=12x-8 |

Equations solver categories